2014
DOI: 10.1186/2193-1801-3-295
|View full text |Cite
|
Sign up to set email alerts
|

Human kallikrein-2 gene and protein expression predicts prostate cancer at repeat biopsy

Abstract: PurposeThe human kallikrein-2 (hK2) protein and two single nucleotide polymorphism (SNPs) (rs2664155, rs198977) of the gene are associated with prostate cancer risk. We examined whether hK2 protein and gene SNPs predict prostate cancer at the time of repeat biopsy.MethodsWe prospectively offered a repeat biopsy to men with a negative prostate biopsy performed for a PSA >4.0 ng/mL or abnormal Digital Rectal Exam (DRE) between 2001–2005. We genotyped and measured serum hK2 levels in 941 men who underwent a repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Many experiments have confirmed that the serum hK2 is helpful to the detection of Pca and prognosis. [ 12 ] We found when the cut-off is 268.33, the sensitivity was 25.6% and the specificity was 96.5% of hK2, with an AUC of 0.607 (95% CI: 0.493–0.721), the results was familiar with other studies. What's more, for those patients with PSA “grey area,” the sensitivity was up to 60.0% and the specificity to 94.3%.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Many experiments have confirmed that the serum hK2 is helpful to the detection of Pca and prognosis. [ 12 ] We found when the cut-off is 268.33, the sensitivity was 25.6% and the specificity was 96.5% of hK2, with an AUC of 0.607 (95% CI: 0.493–0.721), the results was familiar with other studies. What's more, for those patients with PSA “grey area,” the sensitivity was up to 60.0% and the specificity to 94.3%.…”
Section: Discussionsupporting
confidence: 59%
“…Human kallikrein 2 is a kind of serine protease, which possesses 79% of the amino acid sequence identical with PSA, is also a novel biomarker for Pca. [ 11 , 12 ] hK2 is mostly produced in the prostate, secreting with the form of proenzyme in the body and outside the cell is activated into active enzymes. hK2 exists in blood, semen and saliva, and other bodily fluids, furthermore, 80% to 95% of hK2 in the blood exists in the free form.…”
Section: Discussionmentioning
confidence: 99%
“… 34 The kallikreins KLK2 and KLK3 are a subgroup of serine proteases implicated in carcinogenesis and have potential roles as novel cancer biomarkers. 35 PSA protein is the product of the KLK3 gene used in the diagnosis and monitoring of prostate cancer. 36 SLC12A1 plays a vital role in the regulation of ionic balance and cell volume.…”
Section: Discussionmentioning
confidence: 99%
“…As such, many SNPs that have been associated with prostate cancer may not even contribute to the actual aberration in function or expression that leads to prostate cancer development and morbidity [35]. Other studies have shown however that some SNPs are in fact involved in the control of expression and function of some genes such as the previously mentioned TMPRSS2 [36,37].…”
Section: Single Nucleotide Polymorphisms (Snps)mentioning
confidence: 99%